Rocas que narran la historia: inventario del patrimonio geológico del Valle Sagrado de los Incas y su potencial como geoparque - Huaman Huillca, Edilson (2025)
This study was carried out using the PMBOK methodology proposed by Project Management Institute (PMI) in 2008, which includes inputs, tools, techniques, and outputs, with the objective of systematizing and cataloging the geological heritage of the Sacred Valley of the Incas. A methodology adapted to the region was proposed, consisting of 10 stages. The results obtained at each stage are consistent with the criteria proposed by UNESCO for the creation of the Sacred Valley Geopark. A total of 77 geosites were identified, of which 34 were selected for the final inventory based on a rigorous evaluation and characterization according to their Scientific Value, Educational Potential, Touristic Potential, and Risk of Degradation, considering their geological and geomorphological characteristics. Among the most significant findings is the close relationship between geological and cultural heritage, as well as the detailed description of each geosite, incorporating aspects of geotourism, management, and geoconservation. Additionally, geomiradors (viewpoints) and georoutes were identified and proposed to enhance the value of the territory.